2020
DOI: 10.3390/agronomy10020210
|View full text |Cite
|
Sign up to set email alerts
|

Glycinebetaine Enhances Osmotic Adjustment of Ryegrass under Cold Temperatures

Abstract: Perennial (Lolium perenne L.) and annual (L. multiflorum) ryegrass are important species for landscape (e.g., turf) and agricultural (e.g., pasture systems) uses. Abiotic stresses limit the survival, growth, and/or appearance of these species. The synthesis and accumulation of quaternary ammonium compounds (QACs) such as glycinebetaine (GB) are an adaptive response to abiotic environmental stresses in some species. Both L. perenne and L. multiflorum are GB-accumulating species, and exogenous application of GB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…GB is assumed to have several adaptive effects on drought and salt stressed plants. The role of GB is to maintain water content in plant cells by lowering solute potential under osmotic stress [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…GB is assumed to have several adaptive effects on drought and salt stressed plants. The role of GB is to maintain water content in plant cells by lowering solute potential under osmotic stress [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The foliar application of GB induced the salinity tolerance in onions by up-regulating antioxidative defense systems, including non-enzymatic (glutathione and ascorbic acid), enzymatic [CAT, SOD, and ascorbate peroxidase (APX)] antioxidants, photosynthetic efficiency, and increasing the membrane stability index (Rady et al, 2018 ). Similarly, the exogenous application of GB enhanced the cold stress tolerance of perennial ( Lolium perenne L.) and annual ( L. multiflorum ) ryegrass (Mickelbart and Boine, 2020 ) along with the drought tolerance of sweet potatoes ( Ipomoea batatas ) (Tisarum et al, 2020 ). A comparative analysis of the exogenous application of abscisic acid (ABA) and GB on enhancing the drought tolerance of Axonopus compressus revealed that GB was more effective than ABA.…”
Section: Glycine Betaine and Betaine Aldehyde Dehydrogenase ( mentioning
confidence: 99%